Factors that lead to customer satisfaction towards online banking / Nur Shafeeka Jailani and Wan Nur Dini Sabrina Wan Azmi - Jailani, Nur Shafeeka; Wan Azmi, Nur Dini Sabrina (2018)
Banks are separated into several forms in Malaysia such as central banks, Islamic banks and commercial banks, The banking industry is one of the most significant industries m this Malaysia and most banks have their own banking websites as move to increase their effectiveness. Online banking brings convenience to customers and encourages customers to conduct transaction more efficiently and easily through the banking website. Online banking also benefits the bank in reducing the operational cost. With the rapid growth of the Internet, banks have changed the way financial services are being design and delivered. Online banking has gradually replaced the traditional based counter-form of banking because it offers many advantages amongst which are improved efficiency of payment and other financial services. According Chong cl at. 2015, online banking lias been recognized and well-known around the world. Thus, based on Guru etat. (2001), in order to compete in the online banking institutions, this oilers new opportunities and challenges to banking institutions around the world. Other than that, most of the banks are available with the internet facilities. Customers are able to accomplish their banking accounts or transactions with a single click via the internet connection through these internet facilities.